Inovasi Keterampilan Rumah Tangga: Pelatihan Pembuatan Sabun Cuci Piring Cair bagi Ibu Rumah Tangga di Tegalsari - Susanti Sundari; Farisya Diansyafira; Dita Meliana; Thabita Carolina; Ni Gusti Ayu Novita Sari (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
Women's economic empowerment is essential for strengthening household welfare, particularly among homemakers with limited access to productive skills. This community-engagement program aimed to improve women's competence in Pekon Tegalsari in producing, packaging, and labeling hygienic dishwashing liquid, as well as in calculating basic production costs. Participatory Action Research (PAR) positioned 13 participants as active partners in theoretical instruction, demonstration, hands-on production, packaging, labeling, and evaluation. Pre-test results showed that 12 participants (92.31%) scored at least 8 of 10, whereas only eight (61.54%) had prior practical experience. After training, all participants (100%) answered every post-test item correctly and produced dishwashing liquid according to the prescribed procedure. The integration of instruction, demonstration, and direct practice strengthened technical competence, increased awareness of the product's economic potential, and reinforced participants' confidence in applying the skills independently. The program, therefore, provided an initial foundation for household-based microenterprise development by improving product presentation and basic cost management.